Dietary astragalin confers protection against lipopolysaccharide-induced intestinal mucosal barrier damage through mitigating inflammation and modulating intestinal microbiota - Tang, Enhui; Lin, Huan; Yang, Yihao; Xu, Jiawen; Lin, Baiwen; Yang, Yang; Huang, Zijian; Wu, Xinlan (Frontiers in Nutrition, 2024)
Introduction The intestinal mucosal barrier (IMB) damage is intricately linked with the onset of numerous intestinal diseases. Astragalin (AS), a flavonoid present in numerous edible plants, exhibits notable antioxidant and anti-inflammatory properties, demonstrating a promising impact on certain intestinal ailments. In this study, our objective was to investigate the protective effects of AS and elucidate the underlying mechanisms by which it mitigates lipopolysaccharide (LPS)-induced damage to the IMB in mice. Methods During the experimental period, mice were subjected to a 7-day regimen of AS treatment, followed by LPS injection to induce IMB damage. Subsequently, a comprehensive evaluation of relevant biological indicators was conducted, including intestinal pathological analysis, serum inflammatory factors, intestinal tight junction proteins, and intestinal microbiota composition. Results Our results suggested that AS treatment significantly bolstered IMB function. This was evidenced by the enhanced morphology of the small intestine and the elevated expression of tight junction proteins, including ZO-1 and Claudin-1, in addition to increased levels of MUC2 mucin. Moreover, the administration of AS demonstrated a mitigating effect on intestinal inflammation, as indicated by the reduced plasma concentrations of pro-inflammatory cytokines such as IL-6, IL-1β, and TNF-α. Furthermore, AS treatment exerted a positive influence on the composition of the gut microbiota, primarily by augmenting the relative abundance of beneficial bacteria (including Lachnospiracea and Lactobacillus murinus), while simultaneously reducing the prevalence of the harmful bacterium Mucispirillum schaedleri. Conclusion AS mitigates LPS-induced IMB damage via mitigating inflammation and modulating intestinal microbiota.